The extent of gender integration within technical guidance on smallholder agricultural commercialization: a scoping review - Silvert, C.J.; Diaz, J.M.; Serra, R.; Cole, S.M.; Warner, L.A.; Robert, T.G. (2025)
This scoping review explored the extent to which gender and women's empowerment concepts have been integrated within technical guidance that extension and development practitioners may use to guide their facilitation of smallholder agricultural commercialization. Past studies show that gender disparities persist and may be exacerbated by shifts in smallholder agricultural commercialization, reinforcing the need for this review. The scoping review and its qualitative analysis of technical expertise and resources found online (e.g., handbooks, guides, etc.) were framed using the Reach-Benefit-Empower-Transform (RBET) framework. Three central conclusions were derived from the review. First, simply analyzing the inclusion of words for gender or women’s empowerment in technical materials does not reveal whether they address gender issues in substantive ways. Second, significant gaps were apparent in the gender integration (or lack thereof) within materials focusing on finance and digitization/e-commerce for smallholder agriculture presenting a critical area for further exploration and investment. Third, significant discrepancies between gender integration in documents with a gender emphasis and documents with other commercialization foci suggest gender experts and experts on other topics in smallholder commercialization often work in silos without effective collaboration.